Analisis Pengelolaan Limbah Medis Puskesmas di Kecamatan Babulu Kabupaten Penajam Paser Utara Berdasarkan Permenkes Nomor 27 Tahun 2017 - Amrullah, Amrullah Aam (Husada Mahakam, 2019)
The amount of medical waste originating from health facilities are expected progressively increasing. Waste generated from medical efforts such as health centers, polyclinics and hospitals are the type of waste which are included in the category of biohazard waste is very dangerous type of environment, where many exiles viruses, bacteria and other harmful substances. This study was conducted to analyze the management of solid medical waste in the public health centers in Kecamatan Penajam Kabupaten Penajam Paser Utara Provinsi Kalimantan Timur. This research is a qualitative descriptive. The object of research is the implementation of medical waste management in health centers and community health centers target sanitarians and janitor. The research variables include the characteristics of medical waste, stage management, medical waste management officers, facilities, SOP and the perceived health impact of medical waste management officers. The results showed solid medical waste management of health centers is not in accordance with the applicable provisions of the color of plastic bags are used not appropriate, storage locations are not eligible, and there are medical waste that is not destroyed by incineration. Medical waste management facilities not adequate ie no conveyance and no incinerators. Medical waste management is done not in accordance with the SOP and SOP is not in accordance with regulations. Medical waste management officers not using PPE. It is advisable to do a lug medical waste with a plastic bag, label and symbol in accordance with existing regulations. Medical waste storage location is advisable to be in a secure area and symbols and labels. Waste disposal is done in the health center in order to keep attention to the existing guidelines to minimize the risk. The need for training on medical waste management and use of PPE.